Karakteristik Ibu Dan Dukungan Keluarga Dengan Kecemasan Menghadapi Persalinan Di Wilayah Kerja Puskesmas Martapura Barat Kabupaten Banjar Tahun 2020 - Rafidah Rafidah; Auliatina Safitri (Jurnal Skala Kesehatan, 2021)
Anxiety is an emotional assessment and response to something dangerous. Pregnancy can be a source of anxiety stressors in third trimester pregnant women related to feelings of fear of pain in childbirth. Some of the factors that cause anxiety, one of which is age, parity, education and family support. This study aims to determine the relationship between age, parity, education and family support with anxiety in third trimester pregnant women in the Work Area of ​​the West Martapura Health Center 2020. The research method used an analytical survey method with aapproach Cross Sectional. The research population of third trimester pregnant women in the Work Area of ​​the West Martapura Health Center in 2020 amounted to 68 people. Sampling is a saturated sample, the number of samples is 68 people. Collecting data using a questionnaire. Data analysis usingtest Chi-Square. The study was obtained from 68 respondents as many as 21 people (30.9%) experienced anxiety in pregnancy, respondents with age at risk were 11 people (16.2%), unsafe parity was 29 people (42.6%), basic education was 38 people (55.9%). The results of statistical tests showed a relationship between age and anxiety (p= 0.002), parity with anxiety (p= 0.001), education and anxiety (p= 0.020), family support and gold (p= 0.001). Mother's characteristics (age, parity, education) and family support with anxiety facing childbirth in the Work area of ​​the West Martapura Health Center in 2020. Keywords : Anxiety, Age, Parity, Education, Family Support